PERAN GURU AGAMA KATOLIK DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK KELAS VII SMP NEGERI 01 PANCURBATU - Erikson Simbolon; Florencia Surabina (CV. ADIBA AISHA AMIRA, 2024)
The religious Character of students becomes a special problem in class VII of SMP Negeri 01 Pancur Batu in carrying out Catholic Religious Education learning activities. The background of this research is because young people today are pampered with the ease of accessing various negative and free and unlimited information via the internet. the ease of access to the internet has influenced the mindset and the character of students. This is due to the lack of wisdom of students in Accessing the internet. So that it has an impact on the development of the religious character of students in the classroom during the learning processes. This Research uses a Qualitative Approach. Researchers collected data through observation, interview, and documentation. The research targets include the Catholic Religion Teacher and Students in class VII of SMP Negeri 01 Pancur Batu. The results of this study show how the teacher plays a role and becomes a role model or example to students, showing results to students to have more awareness or love and more good character. This can be seen from students who already understand religious character and have practiced respectful, polite, friendly, honest behavior, and have a sense of love for others.